Strategies to promote sustainability in higher education institutions: A case study of a federal institute of higher education in Brazil. Issue 7 (6th November 2017) - Berchin, Issa Ibrahim; Grando, Vanessa dos Santos; Marcon, Gabriela Almeida; Corseuil, Louise; Guerra, José Baltazar Salgueirinho Osório de Andrade
Abstract : Purpose: This paper aims to analyze strategies that promote sustainability in higher education institutions (HEIs), focusing on the case study of a federal institute of higher education in Brazil. Design/methodology/approach: The research was based on a scientific literature review on sustainability in HEIs, to identify the recurrent actions for sustainability in these institutions; and a case study of a federal institute of higher education in Brazil, to illustrate how these actions are being implemented by HEIs. Findings: Concerns about sustainability, prompted by the Brazilian federal legislature, led federal HEI to change its internal processes, infrastructure and organizational culture toward sustainability. Practical implications: The findings presented in this study, more specifically the sustainability plan of the Federal Institute for Education, Science and Technology of Santa Catarina, aligned with the recommendations proposed, can be used and replicated in other HEIs. Originality/value: Scientific literature about organizational changes led by sustainability concerns, in HEIs specifically, still needs more attention in the academia. By addressing the case of a Brazilian public institution of higher education, this paper contributes to the literature on sustainability in higher education by reporting the process of implementation of a sustainability plan.